Art of Living as a Tragic Fate: An autobiographical reading of Friedrich Nietzsche’s Ecce Homo - Voragen, Roy (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
Writing, for Nietzsche, is a very personal endeavor. Nietzsche became Nietzsche through the acts of writing, reading what he has written and re-writing. For a decade or so I have struggled with Nietzsche; I read his books, I wrote essays and I taught on Nietzsche. In this essay I try to answer a personal question: what does reading his books and writing and teaching on Nietzsche mean for who I am today? The second question this essay deals with is how my experiences with Nietzsche’s work influence my view of art. Art is in this essay understood in two ways: first and foremost as the art of living, i.e. how to become what one is, and in the final part of the essay in the narrow sense, i.e. the fine arts.